Epidemiological Profile of Extremity Fractures and Dislocations in Road Traffic Accidents in Kashan, Iran: a Glance at the Related Disabilities - Mahdian, Mehrdad; Fazel, Mohammad R; Sehat, Mojtaba; Khosravi, Gholamreza; Mohammadzadeh, Mahdi (Archives of bone and joint surgery, 2017)
Apart from the mortality, road traffic injuries are associated with significant morbidities. This study has aimed to examine the pattern of traffic accident-related extremity fractures/dislocations and their related disabilities. A retrospective hospital-based study was conducted to assess the characteristics of limb fractures/dislocations among road traffic accident victims registered in Trauma Research Center registry of Kashan University of Medical Sciences, Kashan, Iran, during 2012-2013. Age and sex distribution, cause of injury, and site of fractures/dislocations were recorded. Years lived with disability (YLD) was calculated as a scale to measure the disability. One-way ANOVA and chi-square tests were used for data analysis. From a total of 962 subjects, 812 (84.4%) were males (the male/female sex ratio: 5.4:1). The mean age of victims was 32.7±17.9. Leg (37%) and forearm (19%) fractures were the most frequent fractures. Shoulder dislocations were among the most affected joints accounting for 36.6% of the cases. The total calculated YLD was 135.6 (34.4 for temporal and 101.2 for lifelong disabilities, and totally 117.3 and 18.3 for males and females, respectively). The highest YLD was for motorcyclists (104) and while the most YLD was for 15-29 years (68.2). Young men motorcyclist accidents are a major problem in Kashan region. Generally, they have been accounted for the highest YLD due to fractures/dislocations, especially in lower extremity. Although the calculated YLD will be decreased with increasing age, the elder people also had the high rate of traffic-related limb injuries.